Spatial perception and vestibular function - Keisuke Kushiro (Japanese Society of Physical Fitness and Sports Medicine, 2012)
Humans sequentially perceive spatial information surrounding them when performing intended motor movements. Precise spatial information is constructed in the brain by integrating sensory information such as visual, vestibular, and somatosensory inputs. Visual input is considered an essential source of stable spatial perception in our daily lives. In addition, and in parallel with visual function, vestibular and somatosensory systems have important roles in spatial perception, particularly when unconscious. Although the vestibular system is not considered one of the "five senses" of human sensation, this system serves a couple of important functions. One important function is the prompt stabilization of the head and body against outer disturbances. In addition, vestibular signals are utilized in the higher order of the brain for construction of three-dimensional spatial perception. In this review, the functional properties, as well as the neural system, of the vestibular system are introduced in relation to spatial perception.